SISTEM INFORMASI PENYEWAAN LAPANGAN PADA GELANGGANG OLAH RAGA (STUDI KASUS GELANGGANG OLAH RAGA DI DKI JAKARTA) - Ari Maulana; Tri Wahyu Widyaningsih (Politeknik Negeri Indramayu, 2023)
Sport is a physical activity that is carried out regularly to maintain health and stamina. Therefore, the government provides facilities for the community in the form of Sports Arena (GOR). GOR management is managed by the government in each region, so the handling of GOR in each region is different. This study designed a badminton court rental service system where the previous system was still done manually. People who want to rent must come to the location of the badminton court in advance to search for a schedule and rent a badminton court. To make it more accessible, the system was developed using a web-based application with an Agile Extreme Programming model. That is a software development method that begins with the Planning, Design, Coding, and Testing stages. This Information System can provide information regarding badminton courts, badminton court search features and badminton court bookings. Alpha test results show that the system built is running well. Then the results of beta testing from the results of the questionnaire using the Likert scale analysis method and based on the Kaplan and Norton models show that from 20 users and managers the average satisfaction result is 3.36 which is at the 'quite satisfactory' level. Based on the results of the alpha and beta testing, it can be concluded that this web-based rental information system is appropriate and meets the needs of users and badminton court managers.